Analysis of heat loss in wall insulators and sterilizer door covers in palm oil processing factories - Aulia Suryaning Putri; Dessy Agustina Sari (International Journal of Basic and Applied Science, 2023)
The main stage of crude palm oil (CPO) production takes place in the boiling process, which involves the role of sterilizer equipment. One of the ideal standards for producing CPO is to have an oil yield value in the range of 22.5-23.5%. However, the palm oil processing industry only found an oil yield of 20.25%. The decrease in yield was due to the steam pressure entering the sterilizer not being up to standard. Therefore, the purpose of this study is to analyze the effect of steam exiting the sterilizer or heat loss with the help of mathematical equations (including the Nusselt number and Rayleigh number) by utilizing field data. This research in the palm oil processing industry gave the highest result for heat loss at peak III of 58,074 kJ with Bunches of Fresh Fruit (BFF) boiling conditions at 2.7 bar and 130°C and a process time of 600 seconds. The resulting CPO oil yield was 20.25% (a decrease of about 10–14% from the production standard). The industry, together with a third party (a maintenance consultant from outside the company), assessed the need to maintain a continuous production process and a decrease in oil yield (2.25–3.25%). The yield gap leads to solving the problem through an operating condition optimization approach. The treatment that can be applied is equipment extension through the installation of double-glazed windows on the sterilizer equipment to minimize heat loss. This consideration is the best option considering the continuous palm oil production process and is able to prevent partial or total shut-down activities.